Phenotypic plasticity in the health status of western Mediterranean sardines. Estimation of spawning quantity and quality - Frigola-Tepe, Xènia; Ollé-Vilanova, Judith; Schull, Quentin; Caballero-Huertas, Marta; Viñas, Jordi; Muñoz, Marta (Frontiers in Marine Science, 2025)
The European sardine exhibits drastic changes in body condition, growth, and reproduction outputs with fluctuating environments, leading to trade-offs in life history traits. This study aimed to compare the health status of sardines collected in four areas of the western Mediterranean facing different environmental and anthropogenic pressures (the Gulf of Lion, the northern Catalan coast, the southern Catalan coast, and the Alboran Sea). A decreasing gradient was observed in the somatic condition of sardines from south to north in the western Mediterranean. Sardines from the Gulf of Lion exhibited poor body condition throughout their reproductive cycle and reached relatively small adult sizes. These sardines did not waste energy for growth but favored energy investment in reproduction, which in turn could lead to increased mortality after the spawning season. Moreover, sardines from the Alboran Sea tended to exhibit satisfactory conditions throughout their reproductive cycle, using mesenteric fat almost as a unique energy resource for reproduction investment. These sardines probably invested energy in both reproduction and growth, as energetic resources were abundant. Moreover, they fed intensively during the winter spawning season and maintained high body condition throughout their reproductive cycle, which suggests an income breeding strategy. Along the Catalan coast, sardines followed a capital breeding strategy, as they developed gonads using the energy stored during the primary production blooms of spring. Although they depleted a considerable part of their tissue fat and mesenteric fat contents during the spawning season, they could invest energy in growth. Finally, under the highest levels of relative batch fecundity in December, sardines produced the best egg quality, which could likely ensure greater larval survival and good recruitment.